Assessing the relationship between DNA methylation and gene expression in germ cell tumours - Alhazmi, Safiah (2016)
Germ cell tumours (GCTs) are a class of tumours classified histologically into two main types: seminoma and non-seminoma. Prior studies revealed that there is a significant difference in global DNA methylation between those two types, where non-seminomas represent more differentiated cells and exhibit a high level of methylation compared with seminomas that resemble the precursor cells of GCTs. A number of studies have reported that silencing of genes by DNA methylation is a common phenomenon in many types of cancer. However, the silenced genes and the genomic targets that are methylated in GCTs have not yet been systematically identified. Furthermore, many methylation studies in GCTs do not include the level of gene expression in their investigation. We hypothesized that the methylation of genes might play an important role in gene silencing in GCTs, so the main focus of this thesis was studying the relationship between the gene methylation and gene expression in GCT cell lines representing seminoma and non-seminoma. We analysed genome methylation and gene expression of these cell lines using the Illumina infinium Human Methylome 450 bead chip system and Affymetrix Gene Chip Human Genome U133 Plus 2.0 arrays, respectively. We also compared our results with gene expression data from primary tumours in order to identify which events were shared in primary GCTs tumour. qPCR analysis was carried out after treatment of cells with the demethylation agent, 5-aza-2-deoxycytidine, to confirm that expression of identified genes was regulated by methylation. These analyses showed that differential methylation of CpG islands between seminoma and non-seminoma cell lines correlated well with differential gene expression and revealed that hypermethylation of CpG islands near the transcriptional start site was more strongly correlated with low gene expression than was methylation of other regions. Meanwhile, methylation analysis identified uniquely methylated genes and features for each cell line, which may imply an underlying mechanism of their development. One-hundred and forty-seven silenced genes which exhibited a difference in methylation and expression between seminoma and non-seminoma cell lines were identified, some of these genes were also differentially expressed in primary tumours. Re-expression of selected silenced genes in non-seminoma cells after treatment with 5-aza-2-deoxycytidine confirmed that methylation played a role in gene silencing. Some of the genes identified are closely associated with pluripotency and implicated in chemosensitivity (PRDM14, KLF4, TDRD12, DDX43, MNS1, and RBMXL2). Silencing of these genes could therefore account for the progression process from seminoma to non-seminoma. PRDM14 was given special attention as it plays an important role in germ cell development and maintenance of germ cell pluripotency. The role of PRDM14 in GCT biology was studied, revealing that high expression of PRDM14 in combination with 5-aza-2-deoxycytidine treatment increased the response of cells to chemotherapy compared with those that had low levels of PRDM14. In addition, this study supports a growing body of literature on PRDM14 suggesting that this gene plays a critical role in DNA demethylation.